Tunasniyoj, a dinosaur tracksite from the Jurassic-Cretaceous boundary of Bolivia - Apesteguía,Sebastián (2011)
Here we report a superbly preserved and profusely represented five-ichnotaxa dinosaur track assemblage near Icla village, 100 km southeast of Sucre, Bolivia. As preserved in reddish Jurassic-Cretaceous boundary aeolian sandstones, this rich and uncommon assemblage is, additionally, the oldest dinosaur tracksite for Bolivia. Four trackmakers were identified in the area: three quadrupedal and one bipedal, all of them with tracks of around 35 cm in lenght. One of the quadrupedals is represented by no less than five adult individuals (ichnotaxon A), and four purported juveniles (ichnotaxon B) walking in association. The other two quadrupedals (ichnotaxa C and D) involve four trackways, and the last, the bipedal trackmaker (ichnotaxon E), is represented by one trackway. The five ichnotaxa represented in the "Palmar de Tunasniyoj" could be tentatively assigned to the following trackmakers: Ichnotaxa A and B are assigned to basal stegosaurians; ichnotaxon C to a basal tyreophoran, perhaps related to the ankylosaur lineage; ichnotaxon D to the Ankylosauria, and ichnotaxon E to Theropoda. The Tunasniyoj assemblage, the oldest dinosaur tracksite for Bolivia, includes the oldest known evidence assigned to ankylosaurs and stegosaurs for South America.